Semiotic Shortcuts. The Graphical Abstract Strategies of Engineering Students - Guinda, Carmen Sancho (HERMES - Journal of Language and Communication in Business, 2016)
Graphical abstracts are representative of the rising promotionalism, interdisciplinarity and changing researcher roles in the current dissemination of science and technology. Their design, moreover, amalgamates a number of transdisciplinary skills much valued in higher education, such as critical and lateral thinking, and cultural and audience awareness. In this study, I investigate a corpus of 56 samples of graphical abstracts devised by my aeronautical engineering students, to find out the ‘semiotic shortcuts’ or encoding strategies they deploy, without any previous instruction, to pack information and translate the verbal into the visual. Findings suggest that their ‘natural digital-native graphicacy’ is conservative as to the medium, format and type of representation, but versatile regarding particular meanings, although not always unambiguous or register-appropriate. Consequently, I claim the convenience of including graphicacy/visual literacy and some basic training on graphical abstract design in the English for Specific Purposes and the disciplinary English-medium curriculum.